Causal relationship between gut microbiota and prostate cancer contributes to the gut-prostate axis: insights from a Mendelian randomization study - Li Wang; Yong-bo Zheng; Shan Yin; Kun-peng Li; Jia-hao Wang; Er-hao Bao; Ping-yu Zhu (Discover Oncology, 2024)
Abstract Background Changes in gut microbiota abundance have been linked to prostate cancer development. However, the causality of the gut-prostate axis remains unclear. Methods The genome-wide association study (GWAS) data for gut microbiota sourced from MiBioGen (n = 14,306), alongside prostate cancer summary data from PRACTICAL (n = 140,254) and FinnGen Consortium (n = 133,164). Inverse-variance-weighted (IVW) was mainly used to compute odds ratios (OR) and 95% confidence intervals (Cl), after diligently scrutinizing potential sources of heterogeneity and horizontal pleiotropy via the rigorous utilization of Cochran's Q test, the MR-PRESSO method, and MR-Egger. We used meta-analysis methods in random effects to combine the Mendelian randomization (MR) estimates from the two sources. Results The pooled analyses of MR results show that genus Eubacterium fissicatena (OR = 1.07, 95% CI 1.01 to 1.13, P = 0.011) and genus Odoribacter (OR = 1.14, 95% CI 1.01 to 1.27, P = 0.025) were positively associated with prostate cancer. However, genus Adlercreutzia (OR = 0.89, 95% CI 0.83 to 0.96, P = 0.002), Roseburia (OR = 0.90, 95% CI 0.83 to 0.99, P = 0.03), Holdemania (OR = 0.92, 95% CI 0.86 to 0.97, P = 0.005), Flavonifractor (OR = 0.85, 95% CI 0.74 to 0.98, P = 0.024) and Allisonella (OR = 0.93, 95% CI 0.89 to 0.98, P = 0.011) seems to be a protective factor for prostate cancer. Sensitivity analysis found no significant heterogeneity, horizontal pleiotropy, or reverse causal links in all causal associations. Conclusion This MR study lends support to a causal relationship between genetically predicted gut microbiota and prostate cancer. Research on the gut-prostate axis, along with further multi-omics analyses, holds significant implications for the prevention and treatment of prostate cancer.